PERSPECTIVE OF PUBLIC POLICY EVALUATION: THE MARRIAGE AGE MATURITY IN WEST BANDUNG DISTRICT INDONESIA - Engkus Engkus (Universitas Padjadjaran, 2023)
Early marriage is a serious issue that must be addressed immediately due to the numerous consequences of underage marriages, including the loss of future children, domestic violence, mental and biological unpreparedness, divorce, and many others. Many factors, including economic, cultural, juvenile delinquency, and low education levels, influence the occurrence of early marriages in Lembang District, West Bandung District, Indonesia. In this study, data was gathered through interviews, observation, and documentation. The data analysis technique employs data triangulation, which is accomplished in three stages: data reduction, data presentation, and conclusion drawing. The results of the study reveal that the Marriage Age Maturity (Pendewasaan Usia Perkawinan /PUP) program in Lembang District, West Bandung Regency has applied the Policy Evaluation principle to prevent early marriage, but the results have not been optimal.